2016
DOI: 10.1002/elan.201600652
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Electrochemical Biosensor for the Rapid Detection of Saxitoxin Based on Air Stable Lipid Films with Incorporated Anti‐STX Using Graphene Electrodes

Abstract: A miniaturized potentiometric saxitoxin sensor on graphene nanosheets with incorporated lipid films and Anti‐STX, the natural saxitoxin receptor, immobilized on the stabilized lipid films is described in the present paper. An adequate selectivity for detection over a wide range of toxin concentrations, fast response time of ca. 5–20 min, and detection limit of 1 nM have been achieved. The proposed sensor is easy to construct and exhibits good reproducibility, reusability, selectivity, long shelf life and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…A miniaturized potentiometric saxitoxin immunosensor was reported, involving graphene nanosheets with incorporated lipid films and immobilized anti-STX. The achieved LOD was 1 nM, and the method was tested in lake water and shellfish samples [87].…”
Section: Toxinsmentioning
confidence: 99%
“…A miniaturized potentiometric saxitoxin immunosensor was reported, involving graphene nanosheets with incorporated lipid films and immobilized anti-STX. The achieved LOD was 1 nM, and the method was tested in lake water and shellfish samples [87].…”
Section: Toxinsmentioning
confidence: 99%
“…A paper was reported in the literature using a synthetic "receptor" A potentiometric saxitoxin minisensor based on graphene nanosheets with incorporated lipid films and immobilized anti-STX (which is the natural saxitoxin receptor) on stabilized lipid films was recently reported in the literature [32]. A good selectivity and sensitivity for the detection of saxitoxin, fast response times of ca.…”
Section: Applications Of Lipid Film Based Biosensors In Food Analysismentioning
confidence: 99%
“…In one of our papers, electron scanning microscopy (SEM) experiments were performed in order to investigate the mechanism of signal generation [20]. The results have shown that the structure of the polymerized polyacrylate without the lipid has an amorphous structure, but when the lipid is copolymerized, the structure becomes crystalline.…”
Section: Mechanism Of Signal Generationmentioning
confidence: 99%
“…A miniaturized potentiometric saxitoxin sensor on graphene nanosheets with incorporated lipid films and Anti-STX, the natural saxitoxin receptor, immobilized on the stabilized lipid films is described in one of our recent papers [20]. An adequate selectivity for detection over a wide range of toxin concentrations, fast response time of ca.…”
Section: Examples Of Biosensors Based On Lipid Modified Graphene Micrmentioning
confidence: 99%